A Power Factor Corrected Bridgeless Buck–Boost Converter-Fed Brushless Direct Current Motor Drive With Fuzzy Controller - et. al., T. VijayaLakshmi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main aim of this Paper is a power factor corrected bridgeless buck boost converter fed brushless direct current motor drive with Fuzzy controller. In this paper A Fuzzy logic execution in adaptable speed control of BLDC engine is done here. A methodology of rate control of the BLDC motor through monitoring the dc bus voltage of the (VSI) voltage source inverter is utilized with a solitary voltage sensor. The controller should monitor the varied rates and change the yield speed between the varieties of burden. In comparison to other types of motors, the BLDC has many preferences, but the nonlinearity of the BLDC powertrain attributes is not simple due to use of PI controllers. The Fuzzy Logic Control transforms into an appropriate control to tackle this fundamental problem. A Buck boost type converter is intended to operate in the broken current inductor mode in order to provides the inherent PFC at the power supply. The implementation in MATLAB/Simulink was simulated with the proposed method..